Attack or call for help? rapid individual decisions in a group-hunting ant - Hashim, Rosli; Schliessmann, D.; Witte, V. (2010)
Adaptive decision making is an important trait of many animals, especially in the context of foraging. Social animals are able to optimize their foraging behavior individually or on a collective level. In the predatory ant Leptogenys diminuta, scout ants search individually for prey and then decide within seconds whether to attack directly or to recruit a large raiding group for a collective attack. Both strategies have inherent costs and benefits, and the information collected by the scout during prey assessment is crucial for an appropriate reaction. We studied how differences in prey type and size are taken into account by experienced and inexperienced scout ants. Although decisions are made under time pressure and frequently without disturbing the prey, experienced scouts adjusted their raiding strategies in accordance with predicted hypotheses. In contrast, inexperienced scouts preferred a risk-averse strategy by recruiting large raiding groups. After a 4-week learning phase, inexperienced scouts developed raiding strategies equal to experienced scouts, independent of hunting success treatments, suggesting a predetermined behavioral repertoire. Using gas chromatography and mass spectrometry, we studied furthermore whether prey items could be discriminated by chemical cues. Natural prey was distinguishable on a high taxonomic level. In raids on chemically treated dummies, however, responses were not equal to those elicited by real prey. Thus, the ants probably integrate additional information, such as visual or tactile cues, into their decision-making process. Overall, L. diminuta exhibits a remarkably cautious, quick, and adaptive decision-making system in which prey cuticular chemicals are incorporated as informational cues.